Mitigating Hungry Bone Syndrome: Case Reports on Best Practices After Parathyroidectomy - Sarah Firdausa; Luki Kusumaningtyas; Dicky L Tahapary; Wismandari Wisnu; Tri Juli Edi Tarigan (‎ InaJEMD - Indonesian Journal of Endocrinology Metabolic and Diabetes, 2025)
Severe hyperparathyroidism caused by prolonged high levels of parathyroid hormone (PTH) can be managed by removing the gland. One of the critical complications related to parathyroidectomy is hungry bone syndrome (HBS), an emergency morbidity which may be fatal if not promptly and adequately managed. HBS is defined by a rapid and profound decline in serum calcium levels following surgery, as the bones avidly uptake calcium and phosphate in the absence of high PTH levels. It may present as worsened bone pain, carpopedal spasm, severe hypocalcemia, hypophosphatemia, and hypomagnesemia. This report highlights two patients who underwent parathyroidectomy and had different postoperative outcomes for HBS. The first case involves a 19-year-old male who had a history of recurrent fractures and bone pain. In 2019, he got a fracture from a fall, and in 2020, he experienced another fall leading to shoulder dislocation and further fractures. By late 2021, he was diagnosed with severe hyperparathyroidism due to parathyroid adenoma and the gland was removed. Two days post parathyroidectomy, he developed HBS. He was treated with calcium and vitamin D supplementation. Over two years of follow-ups, his bone density and mobility improved significantly. The second case involves a 46-year-old male with uncontrolled hypertension and chronic kidney disease stage 5 on hemodialysis, presenting with bone pain and deformities. This patient had a long-standing history of bone pain and fractures. He underwent a similar surgical intervention for tertiary hyperparathyroidism but did not develop HBS postoperatively. Careful perioperative monitoring of electrolytes, vigorous supplementation of calcium and vitamin D, and the use of antiresorptive therapies before surgery had been employed. These cases underline the variety of postoperative outcomes and the importance of tailored management strategies. Early intervention, appropriate surgical management, and aggressive postoperative supplementation are crucial to prevent and manage HBS in patients with severe hyperparathyroidism. Multidisciplinary approach and the utilization of various imaging modalities and intraoperative PTH monitoring are mandatory in managing such complex cases. Applying these approaches will reduce the risk of HBS while guaranteeing excellent postoperative care for individuals following parathyroidectomy.